Global communications strategy on rangelands and draft action Plan for 2022-2024 - Flintan, Fiona E.; Buemi, M.; Victor, Michael (International Livestock Research Institute, 2022)
The strategic goal of this strategy and the communication supported therein, is to draw attention to the importance of rangelands (and rangeland communities) and their protection and restoration. This will be done through a coordinated effort by ILRI working with international and national partners as part of ILRI’s global livestock for advocacy development (GLAD) work), engaging mainly outside the livestock sector to improve investments and decisions. This strategy will be implemented by the Sustainable Livestock Systems4 programme, with support form ILRI’s Communications and Knowledge Management Team.